IMPLEMENTATION OF JAKARTA ENTREPRENEUR PROGRAM IN CULINARY MSME DEVELOPMENT UNDER GOVERNOR REGULATION 2/2020 - Hutauruk, Rahel; Nababan, Roida; Hertati Gultom, Meli (ANAYASA : Journal of Legal Studies, 2025)
This study aims to analyze the implementation of the Jakarta Entrepreneur Program in supporting the development of culinary MSMEs by the PPKUKM Office based on Governor Regulation No. 2 of 2020 and assess its effectiveness in encouraging the growth of culinary MSMEs. This study uses a normative legal research method with an analysis approach to legal norms, principles, and doctrines contained in laws and regulations as well as legal literature. This method relies on secondary data to evaluate legal rules and provide a systematic understanding of the policies implemented. The study results show that the Jakarta Entrepreneur Program aims to support the development of MSMEs, especially in the culinary sector, to improve community welfare and reduce poverty. This program covers seven main stages (7Ps), namely registration, training, mentoring, licensing, marketing, financial reporting, and financing. Although the program has succeeded in increasing MSME participation and providing free facilities such as packaging design and certification, various obstacles remain. Some of the main challenges include a limited understanding of entrepreneurship, technical problems, and the need to improve the effectiveness of the program. To increase the impact of the program, improvements are needed in training specifications, financial reporting systems, and ongoing evaluations to ensure the effectiveness and sustainability of the program in the long term.